Scientific Literacy Assessment Instrument on Addictive Substances Topic in Ethnoscience Integrated Inquiry Based-Learning - Purwanti Widhy Hastuti; Putri Anjarsari; Sri Yamtinah (Journal of Science Education Research, 2022)
A skill needed in the 21st-century learning is scientific literacy (SL). Ethnoscience integrated inquiry-based learning (IBL) is expected to train the SL. The SL ability can be measured using an instrument. The purposes of the research were i) to produce a valid and reliable instrument on the ability to measure the SL using ethnoscience integrated IBL and ii) to know the item analysis results of the item test. The research method used was research and development (RnD) with instrument development. Data collection techniques were questionnaires and tests. The instruments of data collection were validation sheets and assessment instruments on SL ability. The data analysis technique used was both descriptive qualitative and quantitative techniques. The qualitative analysis was aimed to determine the product quality using Aiken's V theory. The quantitative analysis aimed to determine the product quality empirically using Rasch model. A valid and reliable instrument was produced with 15 test items for additive substances topic with integrated ethnoscience in learning.